TOTALITARIAN THREATS OF DIGITAL AGE - Tymchyshyn, B. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The growing challenges of the emergence of totalitarianism of a new format generated by the information age are investigated. The features of the new totalitarianism are revealed. Classical totalitarianism manifested itself in the form of a totalitarian state and used measures to ensure control over people, including terror. Today, totalitarianism is much more hidden in nature, because it makes use of modern fashion for the «transparency» of everything (the state, companies, personal life) and the tools for obtaining information about people and events. The trend of the state monopoly leaving the sphere of control, storing personal information, and its manipulation, but it creates conditions for private organizations to initiate their own mechanisms with the same tasks is analyzed. It is explained that these may be algorithms that exploit human behavior for a commercial or political purpose. It turns out that in the context of polarization and politicization, commercial organizations have their own agenda, which allows them to demonstrate themselves as a more significant political actor. As an example, the fact is given that the amount of information and its accuracy that large Internet companies possess about their users is likely to surpass in these indicators the information that the most influential intelligence organizations in the past had. Examples of countries in which mass surveillance of their own citizens on the Internet are openly and implicitly gradually deploying digital totalitarianism are considered. The phenomenon of the global outbreak of the COVID-19 pandemic is analyzed as a factor of an attack on human rights for privacy, including individual digital privacy. We study the trends of how, both democratic and authoritarian states, use resonant events and catastrophes as an opportunity to usurp power and gain more control over their citizens. The assumption is made that the digital era implemented the world of cyberpunk in life. It concludes that escape from the situation of elusive privacy through civic activism, pressure groups, and supranational bodies such as the European Union and competition laws.